A synthesis of PIM Flagship 5 activities during 2017–2019 - McLain, R. (Center for International Forestry Research, 2021)
The International Food Policy Research Institute’s Policy, Institutions and Markets’ (PIM) Flagship 5 (PIM5), on the Governance of Natural Resources, addresses the policy and institutional foundations for improved management of natural resources, whether held in common or individually. Research in PIM5 investigates where and how tenure insecurity constrains productive and sustainable management of natural resources, and how community groups and individuals who use the same resources in different ways can govern them, with recognition of multiple claims and the preservation of ecosystem services. This synthesis of research findings and outcomes under the flagship, which primarily covers the period 2017-2019, aims to communicate the salience of the flagship’s research to the development agendas of its current and prospective donors and other partners.